Students’ Adoption of E-Learning Program during Covid 19: Impact on Students’ Engagement and Effective Teaching Method - Y. Johny Natu Prihanto; Simon Petrus Wenehenubun; Raden Nayaka Widhi Mahardika (Conference Series, 2021)
The coronavirus (COVID-19) pandemic has forced universities, as well as governments, businesses and other institutions, to rapidly increase their provision of digital services and in doing so accelerated a number of existing trends. Universities have had to rapidly evolve their digital strategies and the digital literacy and skills of their staff in order to respond to the current demands for online delivery and global digital connectivity. This study aims to find the factors that influence student acceptance of e-learning programs during a pandemic using the Technology Acceptance Model (TAM) approach. The study adopts quantitative research methods and data collected from 300 respondents using convenience sampling methodology. The questionnaire was distributed online to 14 universities in Indonesia. The structural equation model PLS (SEM-PLS) was utilized in this study. The results showed that two major problems rendered the online teaching and learning less effective than expected. One problem was arising from the institutional unpreparedness. Both lecturers and students were involved in struggling with this sudden move on global and untested scale. From the practical point of view, this study offers implications for government and universities to provide policies in the process of adopting e-learning regarding on students’ engagement and effective teaching method.